2020
DOI: 10.1007/978-3-030-47436-2_53
|View full text |Cite
|
Sign up to set email alerts
|

Using Bandits for Effective Database Activity Monitoring

Abstract: Database activity monitoring systems aim to protect organizational data by logging users' activity to Identify and document malicious activity. High-velocity streams and operating costs, restrict these systems to examining only a sample of the activity. Current solutions use manual policies to decide which transactions to monitor. This limits the diversity of the data collected, creating a "filter bubble" over representing specific subsets of the data such as high-risk users and underrepresenting the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Basing a policy solely on a ranking model would be very efficient capacity wise but would lock the decision makers in a filter bubble. This approach is based on solutions to similar problems where test capacity is limited in the realm of security [5]. Saving a major part of the testing capacity for exploration allows both informed decision making and updating the ranking model daily or weekly to maximize the efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing a policy solely on a ranking model would be very efficient capacity wise but would lock the decision makers in a filter bubble. This approach is based on solutions to similar problems where test capacity is limited in the realm of security [5]. Saving a major part of the testing capacity for exploration allows both informed decision making and updating the ranking model daily or weekly to maximize the efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Grushka et al [5] suggested taking a dynamic approach by adding diversity into the monitoring policy to add the ability of exploration for new risks characteristics and demographics. They showed the need to balance exploration of activities and users of low risk with exploitation of high risk scored users and activities.…”
Section: Monitoring As a Sampling Problemmentioning
confidence: 99%
“…Unlike its more general counterpart (RL), MABs have advantages of faster convergences, simpler implementation, and theoretical guarantees [40]. There has also been recent interest in using bandits for database tasks such as monitoring, query optimisation and join ordering [63], [64], [65].…”
Section: Related Workmentioning
confidence: 99%